Ciliary control of adipocyte progenitor cell fate regulates energy storage - Scamfer, Sierra R.; Lee, Mark D.; Hilgendorf, Keren I. (Frontiers in Cell and Developmental Biology, 2022)
The primary cilium is a cellular sensory organelle found on most cells in our body. This includes adipocyte progenitor cells in our adipose tissue, a complex organ involved in energy storage, endocrine signaling, and thermogenesis. Numerous studies have shown that the primary cilium plays a critical role in directing the cell fate of adipocyte progenitor cells in multiple adipose tissue types. Accordingly, diseases with dysfunctional cilia called ciliopathies have a broad range of clinical manifestations, including obesity and diabetes. This review summarizes our current understanding of how the primary cilium regulates adipocyte progenitor cell fate in multiple contexts and illustrates the importance of the primary cilium in regulating energy storage and adipose tissue function.